368 Intravenous Lidocaine for Analgesia in Spine Surgery: A Meta-Analysis of Randomized Controlled Trials. (1st April 2022) - Musa, Arif; Haratian, Aryan; Field, Ryan; Farhan, Saif; Bennett, Collin; Rajalingam, Karan; Cooke, Christopher; Patel, Rakesh; Aleem, Ilyas; Eichler, Martin; Lee, Carlin; Bederman, S. Samuel
Abstract : INTRODUCTION: Spine surgeons face numerous challenges when managing postoperative pain. Although opioid-based management remains the gold standard for the treatment of postoperative pain, opioid consumption is associated with respiratory depression, sedation, pruritus, ileus, nausea, vomiting, and other complications. Lidocaine, a commonly used local anesthetic, also has documented anti-inflammatory, analgesic, and anti-emetic properties. However, its potential as an adjunctive analgesic to minimize reliance on opioid-based therapy remains controversial. METHODS: We conducted a meta-analysis of randomized controlled trials (RCTs) comparing adjunctive intravenous lidocaine to placebo control for pain management after spine surgery. The following databases were searched: PubMed, Clinicaltrials.gov, Cochrane Library, Cumulative Index to Nursing and Allied Health Literature, Clarivate Analytics Web of Science, and World Health Organization International Clinical Trial Register Platform. Postoperative morphine equivalent consumption was compared using standardized mean difference (SMD) and 95% confidence interval (CI). Complications such as nausea, vomiting, pneumonia, delirium, and wound infection were compared using odds ratios (OR) and 95% CI. A p-value < 0.05 was considered statistically significant. RESULTS: A total of three RCTs were included in quantitative synthesis, comprising 235 patients. Cumulative morphine equivalent consumption was not significantly different between lidocaine and control groups (SMD = -1.69, 95% CI: -3.65 to 0.27, p = 0.09) at 48 hours postoperatively. There was no statistical significance between groups in terms of the following adverse events: nausea (OR = 1.40, 95% CI: 0.73 to 2.71, p = 0.31), vomiting (OR = 1.59, 95% CI: 0.76 to 3.34, p = 0.22), pneumonia (OR = 0.31, 95% CI: 0.76 to 3.34, p = 0.48), delirium (OR = 3.00, 95% CI: 0.12 to 76.24, p = 0.51), or surgical site infection (OR = 3.05, 95% CI: 0.12 to 76.54, p = 0.50). CONCLUSION: There was no significant difference between the average cumulative morphine equivalent consumption of patients in the lidocaine and control groups at 48 hours after surgery. The addition of lidocaine did not significantly increase the rates of postoperative complications such as nausea, vomiting, pneumonia, delirium, or surgical site infections.